THE BENIFIST'S AND DEFECTS OF SPECIAL TOOLS ON A COMPACT RING SPINNING MACHINE - M. I. Tairova; Z. A. Islambekova (Modern American Journals, 2025)
Hepatocellular carcinoma (HCC) remains one of the most aggressive malignancies, frequently developing in the context of chronic hepatitis B and C. Over the past 15 years, diagnostic approaches have undergone significant transformations. In addition to traditional methods such as ultrasound and AFP testing, modern strategies incorporate multiparametric MRI and CT, PET-CT, LI-RADS classifications, and artificial intelligence (AI). This paper reviews current approaches to early HCC detection, introduces a regional monitoring model from Uzbekistan, and underscores the integration of digital technologies into routine care.
Keywords: Hepatocellular carcinoma, hepatitis B, hepatitis C, early diagnosis, LI-RADS, ultrasound, MRI, AFP, artificial intelligence, dispensary surveillance, Uzbekistan